CRITICAL DISCOURSE ANALYSIS AS A METHOD OF RESEARCH OF POLITICAL DISCOURSE IN SOCIAL MEDIA - Iarovyi, Dmytro О. (Psychological Prospects Journal, 2017)
The use of the social media diplomacy in political discourse is indisputably getting more popular every year. In this regard social media are the way of reaching each member of the society directly and quickly, allowing them to interact with the audience. This article is aimed at studying the specific features of political discourse in social media and offering the paradigm for its analysis. With this aim, a research of the nature of political discourse in social media is first conducted. It is explained that this discourse is developing in the conditions of high competition for public attention, thus requires to be interactive (even proactive), credible, and reach the target audience. Based on this position, an explanation of the method suitable for the analysis, critical discourse analysis, is provided. Due to the nature of research area, such method seems legitimate for identifying, interpreting and explaining power relations and competition of discourses. Moreover, for the case of Ukrainian society and civil confrontation taking place in it critical discourse analysis could provide necessary answers in terms of avoiding negative consequences.Key words: critical discourse analysis, social media, soft power, civil confrontation.